Komunikasi Strategis Dompet Dhuafa dan Baitulmaal Munzalan dalam Menghadapi Isu - Nursalsabillah, Annisa; Bajari, Atwar; Setianti, Yanti (Universitas Bina Sarana Informatika, 2023)
Every organization needs to develop a strategic communication plan to run a program, including non-profit organizations. In the midst of limited operational funds, non-profit organizations need to think creatively in developing strategic communication designs, so that they are able to maintain their organizations, especially in maintaining public fundraising. In addition to creating a series of structured programs, strategic communication can also help non-profit organizations deal with issues. The purpose of this study is to indicate and analyze the strategic communication implemented by Dompet Dhuafa and Baitulmaal Munzalan when the organizations is facing an issue. The methodology used is a qualitative methodology with a case study method through interviews and literature studies. The results of the study show that Dompet Dhuafa and Baitulmaal Munzalan Indonesia (BMI) have succeeded in addressing an issue through strategic communication planning, including problem analysis, framing and designing messages, as well as a media approach. Through this form of strategic communication, Dompet Dhuafa and BMI have succeeded in dealing with the issues they experienced and were able to improve the quality of their respective organizations in accordance with the vision, mission and values they have.